PENGARUH MEREK DAN DISTRIBUSI PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM FREN’O PADA PT. RIA TIRTA MAKMUR MEDAN - Cut Fitri Rostina (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This paper is part of the research that investigates the effect of trademark and product distribution on consumer purchasing decisions. The research was conducted at PT. Ria Tirta Makmur Medan and focused on selling Fren'O branded drinking water that is considered less well known in the market and has been a lot of complaining from consumers as indicated by previous research. This study is a quantitative and explanatory descriptive study involving 150 people as a population and 109 people as samples which is performed through the Slovin formula. The method of data collection is through the questioner as the main instrument, while interviews and documents are also used as a complement. Statistical data is processed through multiple regression analysis and the result of the research indicates that trademark and product distribution simultaneously have positive and significant influence to consumer purchasing decision. Partially variable of trademark (brand) and product distribution each has positive and significant influence to consumer purchasing decision, and simultaneously, trademark and product distribution variables give effective contribution equal to 76% to purchasing decision. In conclusion, simultaneously and partially trademark and product distribution significantly influence Fren'O drinking water purchase decision at PT. Ria Tirta Makmur-Medan.